Asesmen Literasi Sains Interaktif Berbasis Kearifan Lokal pada Platform Digital: Perspektif Framework PISA/AKMI: Interactive Science Literacy Assessment Based on Local Wisdom on a Digital Platform: A PISA/AKMI Framework Perspective - Rina Endang Sulistiowati; Evy Nur Rochmah; Juli Firmansyah (ITScience (Information Technology and Science), 2026)
Indonesia's science literacy score in PISA 2022 reached only 383, far below the OECD average of 489. At the local level, the science literacy achievement of *Madrasah Ibtidaiyah* (MI) students in Balikpapan City fell into the